Studi Literatur: Peran Anggaran Tenaga Kerja Langsung dalam Meningkatkan Efisiensi Biaya dan Kinerja Perusahaan - Mutiara Nailah Rizki; Grace Stella Zane Simamora (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of direct labor budgets in improving cost efficiency and financial performance of companies through a literature review approach. This study uses a qualitative method with literature study techniques, namely by reviewing various scientific journals, research articles, and relevant reference books. The results of the study indicate that the preparation of an appropriate direct labor budget has helped companies in optimally planning labor requirements, controlling production costs, and minimizing waste. Cost efficiency achieved through good budget management has had a positive impact on improving the company's financial performance, such as increasing profitability and operational effectiveness. In addition, the direct labor budget has served as a managerial performance evaluation tool through a comparison between budgeted and actual costs. This study concludes that there is a significant relationship between the direct labor budget, cost efficiency, and company financial performance. Therefore, companies are advised to prepare labor budgets systematically and implement effective controls to achieve efficiency and improve financial performance in a sustainable manner.